The Economic Impact of Hurricane Evacuations on a Coastal Georgia Hospital: A Case Study - Desai, Samir P.; Gordon, Jimmy; Harris, Curtis Andrew (Frontiers in Public Health, 2019)
Coastal hospitals are often faced with the challenging decision to either evacuate or shelter-in-place in anticipation of a hurricane predicted to make landfall. The costs associated with hospital evacuation not only include transportation of patients to inland areas, but also the loss of revenue due to interruption of regular operations and the cost of potential damage to the hospital's infrastructure. Financial data provided by Memorial Health University Medical Center (MUMC, Savannah, Georgia) such as average inpatient and outpatient revenues, personnel wages, and transportation costs, were used to estimate the potential economic impact of hurricane evacuations on a coastal hospital. The results indicate that even prior to the arrival of tropical storm force winds, the hospital will incur an estimated total expenditure of approximately 9.5 million which includes evacuation expenses and loss of revenue due to disruption of regular services. In case the hurricane makes landfall, revenue losses will continue to accumulate until the hospital is able to resume regular operations. The cost of relocating patients back to MUMC after the hurricane event and the cost of any hurricane-related damage to the hospital infrastructure must also be taken into consideration. In conclusion, even though hospital evacuation for hurricanes may be unavoidable in certain circumstances, the financial burden placed upon the hospital may be mitigated to a certain extent by forward planning, infrastructure upgrades, and the rapid resumption of regular hospital function.